Characterization of MHC class I in a long distance migratory wader, the Icelandic black-tailed godwit - Pardal, Sara; Drews, Anna; Alves, José A.; Ramos, Jaime A.; Westerdahl, Helena (Immunogenetics, 2017)
The major histocompatibility complex (MHC) encodes proteins that are central for antigen presentation and pathogen elimination. MHC class I (MHC-I) genes have attracted a great deal of interest among researchers in ecology and evolution and have been partly characterized in a wide range of bird species. So far, the main focus has been on species within the bird orders Galliformes and Passeriformes, while Charadriiformes remain vastly underrepresented with only two species studied to date. These two Charadriiformes species exhibit striking differences in MHC-I characteristics and MHC-I diversity. We therefore set out to study a third species within Charadriiformes, the Icelandic subspecies of black-tailed godwits (Limosa limosa islandica). This subspecies is normally confined to parasite-poor environments, and we hence expected low MHC diversity. MHC-I was partially characterized first using Sanger sequencing and then using high-throughput sequencing (MiSeq) in 84 individuals. We verified 47 nucleotide alleles in open reading frame with classical MHC-I characteristics, and each individual godwit had two to seven putatively classical MHC alleles. However, in contrast to previous MHC-I data within Charadriiformes, we did not find any evidence of alleles with low sequence diversity, believed to represent non-classical MHC genes. The diversity and divergence of the godwits MHC-I genes to a large extent fell between the previous estimates within Charadriiformes. However, the MHC genes of the migratory godwits had few sites subject to positive selection, and one possible explanation could be a low exposure to pathogens.